Chrono-Nutrition Has Potential in Preventing Age-Related Muscle Loss and Dysfunction - Aoyama, Shinya; Nakahata, Yasukazu; Shinohara, Kazuyuki (Frontiers in Neuroscience, 2021)
The mammalian circadian clock systems regulate the day–night variation of several physiological functions such as the sleep/wake cycle and core body temperature. Disturbance in the circadian clock due to shiftwork and chronic jetlag is related to the risk of several disorders such as metabolic syndrome and cancer. Recently, it has been thought that shiftwork increases the risk of sarcopenia which is characterized by age-related decline of muscle mass and its dysfunctions including muscle strength and/or physical performance. First we summarize the association between circadian rhythm and the occurrence of sarcopenia and discuss its mechanistic insight by focusing on the muscle function and molecular clock gene in knockout or mutant mice. The clock gene knockout or mutant mice showed early aging phenotypes, including low survival rate and muscle loss. It suggests that improvement in the disturbance of the circadian clock plays an important role in the aging process of healthy muscles. Nutritional intake has the potential to augment muscle growth and entrain the peripheral clock. Second, we discuss the potential of chrono-nutrition in preventing aging-related muscle loss and dysfunction. We also focused on the effects of time-restricted feeding and the distribution of protein intake across three meals.